Short-term echocardiographic follow-up after hospitalization for COVID-19: a focus on early post-acute changes - Honchar, Oleksii; Ashcheulova, Tetiana (Frontiers in Cardiovascular Medicine, 2023)
Background. Impaired physical functional status is one of the typical long-term sequelae of COVID-19 infection that significantly affects the quality of life and work capacity. Minor changes in cardiac structure and function that are unable to cause the manifestation of overt heart failure may remain undetected in COVID-19 convalescents, at the same time potentially contributing to the persistence of symptoms and development of long COVID syndrome. Purpose. To study the typical features and short-term dynamics of cardiac remodeling and possible signs of cardiac dysfunction following hospitalization for COVID-19. Methods. This is a combined cross-sectional and longitudinal cohort study in which 176 hospitalized patients (93 female and 83 male, mean age 53,4 ± 13,6 years) with COVID-19 infection underwent comprehensive transthoracic echocardiography pre-discharge (22,6 ± 7,1 days from the onset of symptoms) with repeated evaluation after 1 month. The control group included 88 age-, sex-, height-and weight-matched healthy individuals, with a subset of those (n = 53) matched to the subset of non-hypertensive study participants (n = 106). Results. Concentric left ventricular geometry was revealed in 59% of participants, including 43% of non-hypertensive subjects; predominantly Grade I diastolic dysfunction was found in 35 and 25% of patients, respectively. Other findings were naturally following from described phenotype of the left venticle and included a mild increase in the absolute and relative wall thickness (0,45 ± 0,07 vs 0,39 ± 0,04, p < 0,001), worsening of diastolic indices (e' velocity 9,2 ± 2,2 vs 11,3 ± 2,6 cm/s, p < 0,001, E/e' ratio 7,5 ± 1,8 vs 6,8 ± 1,7, p = 0,002) and global longitudinal strain (17,5 ± 2,4 vs 18,6 ± 2,2, p < 0,001). No significant improvement was found on re-evaluation at 1 month. Conclusions. Hospitalized patients recovering from COVID-19 were characterized by a high prevalence of left ventricular concentric remodeling, predominantly Grade I diastolic dysfunction, and a mild decrease in the longitudinal systolic function. These changes were less frequent but still prevalent in the nonhypertensive subgroup and largely persisted throughout the 1-month follow-up.